Assessing Ethical Thinking about AI - Goldsmith, Judy; Burton, Emanuelle; Dueber, David M.; Goldstein, Beth; Sampson, Shannon; Toland, Michael D. (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
As is evidenced by the associated AI, Ethics and Society conference, we now take as given the need for ethics education in the AI and general CS curricula. The anticipated surge in AI ethics education will force the field to reckon with delineating and then evaluating learner outcomes to determine what is working and improve what is not. We argue for a more descriptive than normative focus of this ethics education, and propose the development of assessments that can measure descriptive ethical thinking about AI. Such an assessment tool for measuring ethical reasoning capacity in CS contexts must be designed to produce reliable scores for which there is established validity evidence concerning their interpretation and use.